2022
DOI: 10.3390/antiox11030489
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Indicators of Brain Damage Following Pediatric Heart Surgery

Abstract: Pediatric cardiac surgery induces an increased oxidative stress (OS) response. Increased OS is associated with poor neurologic outcomes in neonatal populations with similar patterns of brain injury. We investigated OS and brain injury in infants undergoing heart surgery. Patients 6 months or younger, undergoing cardiac surgery with or without cardiopulmonary bypass (CPB), were included in this prospective, observational study. Patients were divided into infant (30 days–6 months) and neonatal (<30 days) grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In a randomized clinical trial, the results showed that for patients with brain injury, the serum S100B increased during CPB with a peak plasma concentration at the termination of CPB and gradually decreased after 24 hours 30 . In our study, compared to patients without PND, PND (+) patients had an increasing of S100B serum level after TAAR with a peak concentration right after surgery and returned to normal level 24–48 h after surgery, which was consistent with previous studies (Tables S7 , S8 ) 30 , 31 . TAU protein is a microtuble-associated protein found in neurons and is a biomarker for neurodegeneration 32 , 33 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a randomized clinical trial, the results showed that for patients with brain injury, the serum S100B increased during CPB with a peak plasma concentration at the termination of CPB and gradually decreased after 24 hours 30 . In our study, compared to patients without PND, PND (+) patients had an increasing of S100B serum level after TAAR with a peak concentration right after surgery and returned to normal level 24–48 h after surgery, which was consistent with previous studies (Tables S7 , S8 ) 30 , 31 . TAU protein is a microtuble-associated protein found in neurons and is a biomarker for neurodegeneration 32 , 33 .…”
Section: Discussionsupporting
confidence: 92%
“…4 ). Since serum level S100B arrived at peak value around 24 h after cardiac surgery 30 , 31 (Table S7 ), we believed that these three EIT parameters along with S100B had great potential for giving information of neurological damage during surgery for patients with an abnormal preoperative neurological function. Additionally, EIT parameters ΔARV HCA , k HCA and TARV HP had great correlation with variation of serum TAU concentration right after surgery for patients with an abnormal serum level before surgery (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…52 Recent studies found that increased F 2 -isoprostane levels, an indicator of oxidative stress, 49 are associated with adverse clinical outcomes. [53][54][55] To build evidence in this area, we conducted an exploratory RCT to compare biochemical parameters between early versus late PN in term and late preterm infants. We hypothesised that late commencement of PN will achieve lower (and more physiological) levels of plasma phenylalanine and plasma F 2 -isoprostanes on day 4 and day 8 compared with early commencement of PN in term and late preterm infants.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Recent studies found that increased F 2 -isoprostane levels, an indicator of oxidative stress, 49 are associated with adverse clinical outcomes. 53–55 …”
Section: Introductionmentioning
confidence: 99%